Evaluation of the CIPP Model of Innovative Learning Competence of PPG Students in the Field of Guidance and Counseling Study: Case Study at Universitas PGRI Yogyakarta - Esti Setiawati; Hartuti; Murtini (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The development of innovative learning competencies is crucial for In-Service PPG students in Guidance and Counseling to ensure the success of professional learning practices. This study aims to evaluate the innovative learning abilities of PPG students using the CIPP (Context, Input, Process, and Product) evaluation model. This study involved all 30 PPG Guidance and Counseling students. Data collection techniques used documentation, interviews, and questionnaires that had been tested for validity and reliability. Data were analyzed descriptively and quantitatively (mean, percentage, and paired-samples t-test) and qualitatively through content analysis. The results of the study indicate that: (1) the context evaluation is in the good category and in accordance with the implementation guidelines from the Directorate General of Teachers and Education Personnel; (2) the input evaluation is also good, seen from the readiness of students, lecturers, mentor teachers, and facilities and infrastructure; (3) the process evaluation is quite good, with several obstacles in understanding concepts, assessment, service planning, and use of technology; (4) innovative learning competencies in cycles 1 and 2 show very good (36.67%) and good (63.33%) categories; (5) the highest average score was achieved by participants with a work period of 6–10 years; (6) the results of the paired sample t-test showed no difference in the average values of cycles 1 and 2 because the significance (p) was 0.884 > 0.05; and (7) a matriculation program is needed for students from non-Guidance and Counseling backgrounds. These results indicate that the program is running well but still needs improvement in the aspects of mastery of concepts about Guidance and Counseling, assessment, and learning management system (LMS) training. Keywords: CIPP evaluation, PPG, guidance and counseling, innovative learning, program evaluation